2017
DOI: 10.1080/00423114.2017.1342847
|View full text |Cite
|
Sign up to set email alerts
|

Lap time simulation and design optimisation of a brushed DC electric motorcycle for the Isle of Man TT Zero Challenge

Abstract: This works regards the design of an electric motorcycle for the annual Isle of Man TT Zero Challenge. Optimal control theory was used to perform lap time simulation and design optimisation. A bespoked model was developed, featuring 3D road topology, vehicle dynamics and electric power train, composed of a lithium battery pack, brushed DC motors and motor controller. The model runs simulations over the entire 37.73mi or 60km of the Snaefell Mountain Course. The work is validated using experimental data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lap time simulations for motorcycles covering racetracks are described in refs. [51][52][53][54]. Optimum Lap simulations of race vehicles are described in refs.…”
Section: Methodsmentioning
confidence: 99%
“…Lap time simulations for motorcycles covering racetracks are described in refs. [51][52][53][54]. Optimum Lap simulations of race vehicles are described in refs.…”
Section: Methodsmentioning
confidence: 99%
“…Limit-handling is also considered in [56,57], where it is shown that in some scenarios 'drifting' and 'handbrake turning' techniques arise as solutions to the minimum-time OCP. A long-distance track is considered in [58], where the 60 km Snaefell Mountain Course is simulated for the design of an electric motorcycle for the annual Isle of Man TT Zero Challenge. The motorcycle is represented as a mono-wheel with the track elevation considered (without cambering).…”
Section: The 2010smentioning
confidence: 99%
“…Even if various types of motors are still used for competitions (e.g. DC ones 47 ), PM synchronous machines emerged as most used technology due to their potential in terms for maximum performances; design optimization up to the limit of mechanical and thermal integrity being a research topic promoted by racing needs 48 ; interesting, this latest article highlights the possibility to achieve 1000 h durability even for racing electric motor windings, which is a key need for technology transition from motorsport to industrial production.…”
Section: Literature Review On Motors For Evs and On The Role Of Motormentioning
confidence: 99%